2020
DOI: 10.14710/interaksi.9.1.19-30
|View full text |Cite
|
Sign up to set email alerts
|

Media Sosial Dan Literasi Kebencanaan Di Bali

Abstract: After a large, deadly explosive and effusive eruption during 1963-64, Indonesia's Mount Agung on Bali remained quiet until a new eruption began in November 2017 until 2019. Alert Level III (of four levels) remained in effect throughout the period with a 4 km exclusion radius around the volcano.  Massive hysteria occurred when alert level reach the highest level (level IV). The situation get worsed when misinformation has been spreading in social media about Mt. Agung. This research discussing how literate was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…This study uses the Cutlip and Center Communication Planning Model which is the basis for implementing disaster communicsation planning. Research that discusses disaster communication using social media conducted by Gelgel (2020) found that 54% of Balinese people rely heavily on social media Facebook and Instagram to find information on the Mount Agung disaster, so social media is the main source of information. People really believe in social media, so it affects the level of behavior and effectiveness.…”
Section: |mentioning
confidence: 99%
“…This study uses the Cutlip and Center Communication Planning Model which is the basis for implementing disaster communicsation planning. Research that discusses disaster communication using social media conducted by Gelgel (2020) found that 54% of Balinese people rely heavily on social media Facebook and Instagram to find information on the Mount Agung disaster, so social media is the main source of information. People really believe in social media, so it affects the level of behavior and effectiveness.…”
Section: |mentioning
confidence: 99%
“…The results show a positive role in improving the students' disaster preparedness [16], [17]. On the other hand, public knowledge about disasters in general in some disasterprone areas in Indonesia is still low [18] - [23]. Yuliani (2018) states that forest and land fire disasters have a special method of handling them, especially in the disaster prevention process not only involving aspects of disaster risk reduction but also must be accompanied by community empowerment so that the community becomes the main component in this prevention process [24].…”
Section: Introductionmentioning
confidence: 99%